Desenvolvimento e validação de metodologia por HPLC-PDA para monitoração terapêutica dos níveis plasmáticos de zidovudina e efavirenz - SOARES, Amanda Queiroz (2009)
The therapeutic drug monitoring is an important tool to predict the therapeutic efficacy and possible toxicity of antirretroviral agents used to treat infection by human immunodeficiency virus (HIV). The goals of this study was to develop and validate a method of analysis and extraction to quantify the antirretrovirals efavirenz and zidovudine in human plasma, to know the clinical profile and quantify the drugs efavirenz and zidovudine in plasma of volunteers using treatment regimen efavirenz / lamivudine / zidovudine. Blood samples were collected approximately 8 h after administration of AZT and 20 h of the EFZ, were obtained from adult volunteers HIV positive in clinic monitoring at Hospital das Clínicas, Universidade Federal de Goiás and therapeutic protocol EFZ 600 mg once daily and lamivudine 150 mg + zidovudine 300 mg twice a day. After solid phase extraction using cartridge Strata 18E C 500mg, 3 mL capacity, the drugs and internal standard (5 - (4-methylphenyl)-5-fenilidantoína - MPPH) were separated by reversed-phase column ACE 5 C18 100 x 4 6 mm. The mobile phase consisted of acetonitrile and diethanolamine in water (pH 7.8), flow rate 0.5 to 2.0 mL/min and detection at wavelength of 249 nm (EFZ), 267 nm (AZT) and 240 nm (MPPH). The method showed linearity at concentration range of 50 to 5000 ng/mL for both drugs, with recovery of 84 and 92% for EFZ and AZT, respectively. The limit of quantification (50 ng/mL), precision (coefficient of variation <15%) and accuracy (relative errors <15%) are in accordance with requirements of ANVISA. To evaluate the applicability of the method, we analyzed plasma of volunteers (n = 12) with mean plasma concentration of 1960 ± 766 ng/ mL to EFZ and 62.12 ± 16.21 ng/mL to AZT. The method agree analytical parameters suitable for use in therapeutic monitoring of patients using AZT and EFZ